Effects of Herring Fillets and By-Products on Protein Digestibility, Hematology, and Blood Biochemistry in Rats - Olaoluwa Temitope Talabi; Sunday Oyewole Oyedemi; Oluwasanmi Anuoluwapo Adeyemi; Olugbenga Adebawo; Odutola Osilesi; Funmilayo Onajobi (Jurnal Biodjati, 2025)
Protein bioavailability and digestibility are critical for animal growth and health and are influenced by source and processing methods. This study investigated the effects of diets incorporating processed Clupea harengus (herring) fillets and by-products (heads, bones, viscera) prepared by charcoal, wood, or poaching on growth performance, protein quality, hematology, and blood biochemistry in Wistar rats. Forty rats were randomly allocated to eight dietary groups: charcoal-smoked fillet (CSFBD), wood-smoked fillet (WSFBD), poached fillet (PFD), charcoal-smoked by-products (CSHB), wood-smoked by-products (WSHB), poached by-products (PSF), soybean-based positive control, and basal negative control. Diets were fed for 28 days. Smoked by-product diets (CSHB and WSHB) produced significantly higher final body weights (120.86 ± 0.68 g and 105.52 ± 19.94 g) and weight gains (9.14 ± 1.39 g, p ≤ 0.05) than the basal diet (59.55 ± 1.37 g and 5.35 ± 0.25 g). Smoked diets improved feed intake, feed conversion ratio, apparent protein digestibility, and biological value. Hematological parameters remained within physiological ranges across groups; the soybean diet showed the highest RBC (7.8 × 10¹²/L) and hemoglobin (16.3 g/dL), whereas smoked fish diets recorded slightly lower but normal values (RBC 7.0-7.5 × 10¹²/L; hemoglobin 14-15 g/dL). Biochemical profiles revealed that smoked diets reduced serum triglycerides and creatinine, suggesting enhanced lipid metabolism and renal function. Smoking significantly improves the nutritional quality of Clupea harengus fillets and by-products, making them practical, safe, and growth-promoting protein sources for animal nutrition. Inclusion of smoked fish by-products offers a sustainable alternative to conventional plant proteins while supporting metabolic and systemic health